HUBUNGAN PENGETAHUAN TENTANG PERBANKAN SYARIAH TERHADAP MINAT MENABUNG DI BANK SYARIAH: SURVEI PADA SISWA SMK YAYASAN DARUNNA’IM YAPIA PARUNG - Maya Indriani; Ikhwan Hamdani; Syarifah Gustiawati (Kasaba, 2020)
This research examines the relationship of student knowledge on sharia banking on savings interest in sharia banks (in the foundation of Darunna'im Yapia Parung Foundation). This research is based because at this time it is happening more closely the conventional bank concept so that it makes many people use conventional bank services. This study aims to determine the knowledge of students about Islamic banking, and to determine the relationship of knowledge of Islamic banking students on saving interest in Islamic banks. Data collection techniques using questionnaires and interviews. The researcher also collected information through a questionnaire using a Likert scale. The partial test results (T-test) of Islamic banking knowledge variables have a significant effect on saving interest variables as evidenced by the significance value of 0,000 t table of 2.042.